PENERAPAN MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS PUISI SISWA - Sobirin, Sahrul; Nurhasanah, Aan; Nugraha , Febby Fajar (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
There are problems with poetry writing skills and low student learning outcomes in Indonesian language content caused by the use of less varied learning models. This research aims to determine the differences in poetry writing skills between students who study using the Concept Sentence learning model and students who study using the conventional learning model and to determine the improvement in poetry writing skills between students who study with the Concept Sentence learning model and students who study using the learning model. conventional. This research uses a Quasi Experimental Study method. The sample in this research was class V students at SD Negeri 3 Purwawinangun for the 2023-2024 academic year. Data collection techniques use tests. Data analysis techniques use normality tests, homogeneity tests and independent sample t tests. Based on the results of data analysis, it can be concluded that there is a difference in poetry writing skills between students who study using the Concept Sentence learning model and students who study using the conventional learning model and there is an increase in poetry writing skills between students who study with the Concept Sentence learning model and students who study using conventional learning model.